Mapping the Economic Potential of the Community of Teluk Latak Village, Bengkalis District, Bengkalis Regency through an MSMEs: Pemetaan Potensi Ekonomi Masyarakat Desa Teluk Latak Kecamatan Bengkalis Kabupaten Bengkalis Melalui Survey UMKM - Suryanita, Reni; Raihan Arditama Harnedi; Yohannes Firzal; Benny Hamdi Rhoma Putra; Yenita Roza; Poppy Nurmayanti; Harnedi Maizir (Universitas Lancang Kuning, 2024)
This community service activity (PKM) was carried out in Teluk Latak Village, Bengkalis District, Bengkalis Regency, Riau Province. This activity records the socio-economic potential of Teluk Latak Village which focuses on Micro, Small and Medium Enterprises (MSMEs). Although the majority of residents do not experience problems in doing business, some business actors report difficulties, especially in marketing and promoting the products that have been produced. Therefore, this PKM activity collected data on the economic potential in Teluk Latak Village based on information from MSME players. The PKM activity method is carried out through a field survey involving MSME business actors using the interview method and analyzing data related to the economy. The survey results show that the majority of MSME activists in Teluk Latak Village are engaged in weaving. This finding illustrates the strong economic potential, especially in the weaving MSME sector. It is hoped that the results of data collection on economic potential through this PKM activity can be used as a reference for optimal efforts in developing the potential of Teluk Latak Village. The results of the analysis show that improving marketing and promotion strategies can overcome the obstacles faced by some MSME actors, so that economic development in Teluk Latak Village can be carried out holistically, maximizing the potential of the MSME sector and overcoming obstacles that may arise.